2015
DOI: 10.1016/j.transproceed.2015.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Chronic Obstructive Pulmonary Disease and Pulmonary Fibrosis: Prevalence and Hemodynamic Differences in Lung Transplant Recipients at Transplant Center's Referral Time

Abstract: Introduction. Single or bilateral lung transplantation is a therapeutic procedure for endstage lung diseases. In particular, in cases of chronic obstructive pulmonary disease (COPD) and pulmonary fibrosis, patients can be referred to the transplant center late and with important comorbilities. Pulmonary hypertension (PH) associated with lung diseases not only is an index of poor outcome but also is an indication for bilateral procedure. Methods. We conducted a retrospective observational study. We analyzed rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(31 reference statements)
2
4
0
Order By: Relevance
“…Subsequently, typical pathological changes including the damaged alveolar walls and pulmonary bullae were observed after the exposure to both CS and Chry at an earlier stage of experiment, and all these abnormalities in structure have been documented to impair the gas exchange and eventually lead to the dysfunction of lung. 25 Moreover, the collagen depositions, elevated expression of α-SMA and reduced E-cadherin were found in CS + Chry exposed mice at the first 2 week according to our findings. Briefly, it has been reported that myofibroblast accumulation, which is characterized with increased α-SMA and collagen deposition, is a key feature for pathological airway remodeling of COPD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Subsequently, typical pathological changes including the damaged alveolar walls and pulmonary bullae were observed after the exposure to both CS and Chry at an earlier stage of experiment, and all these abnormalities in structure have been documented to impair the gas exchange and eventually lead to the dysfunction of lung. 25 Moreover, the collagen depositions, elevated expression of α-SMA and reduced E-cadherin were found in CS + Chry exposed mice at the first 2 week according to our findings. Briefly, it has been reported that myofibroblast accumulation, which is characterized with increased α-SMA and collagen deposition, is a key feature for pathological airway remodeling of COPD.…”
Section: Discussionsupporting
confidence: 82%
“…and all these abnormalities in structure have been documented to impair the gas exchange and eventually lead to the dysfunction of lung. 25 Moreover, the collagen depositions, elevated expression of a-SMA and reduced E-cadherin were found in CS þ Chry exposed mice at the first 2 week according to our All data were presented as mean + SD of six separate experiments. Versus control group: # P < 0.05, ## P < 0.01, ### P < 0.001, #### P < 0.0001; Versus CS group, *P < 0.05, **P < 0.01, ***P < 0.001, ****P < 0.0001.…”
Section: Discussionmentioning
confidence: 63%
“…RV failure confers a poor prognosis in COPD. 10,11 In our study the incidence of HTN, DM and CAD was 12.34%, 27.16%, 9.87% respectively in the respiratory failure group whereas in the non respiratory failure group the incidence was 19.67%, 26.22% and 9.83% respectively. In a study conducted in Spain by Almagro et al 12 (2010) they found that 55% of the patients had hypertension, 26% diabetes mellitus, 27% chronic heart failure, and 17% ischemic heart disease.…”
Section: Discussionsupporting
confidence: 43%
“…Among hospitalized patients with moderate/severe COPD, 48% demonstrated at least one abnormality of RV structure/function, with RV enlargement being the most common (29.9%) (119). Finally, overt RV failure confers a poor prognosis in COPD (121,122). The treatment of HF due to right ventricle failure in COPD is mostly symptomatic, with diuretics being useful in managing the effects of volume overload (44); other drugs (e.g., those used in primary pulmonary hypertension) do not seem beneficial in patients with COPD (123).…”
Section: Right Heart Failure In Copdmentioning
confidence: 99%